Biopriming Dengan Agens Hayati Pada Benih Padi Terkontaminasi Fitopatogen Drechslera oryzae - Kalay, A. Marthin; Patty, Jogeneis; Talahaturuson, Abraham; Marasabessy, Deasy (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
Fungi Dreschslera oryzae or Helminthosporium oryzae often found in rice seeds and causes brown spot disease (brown spot disease). Symptoms of attack can be seen in nurseries and on mature plants. The aim of the research is to determine the effect of a consortium of biological control agents and secondary metabolites Trichoderma harzianum which is used as biopriming on rice seeds contaminated with D. oryzae. The treatment tried was without biological control agents as a control, consortium T. harzianum and A. chrococcum, consortia of three isolates Bacillus sp, consortium A. chrococcum, A. vinelandi, Azospirillum sp, Pseudomaonas cepacia, Penicillium sp, Acinetobacter sp, and secondary metabolites T. harzianum, designed using a Completely Randomized Design with five replications. The experiment used two methods, namely germinating rice seeds on gauze media and on soil media. The research results found that biopriming with the biological control agents and secondary metabolites T. harzianum on rice seeds, it has the effect of increasing shoot height, shoot fresh weight, seedling fresh weight, root length, and reducing disease intensity. In general, the use of the biological control agents and secondary metabolites T. harzianum has the same effect. The presence of chitinase enzymes and siderophore compounds in biological control agents and secondary metabolites T. harzianum has an effect on reducing disease intensity, while the hormones auxin and gibberellin have an effect on increasing shoot height, shoot fresh weight, seedling fresh weight and root length.